Anticonvulsant valproic acid and other short-chain fatty acids as novel anticancer therapeutics: Possibilities and challenges - Lipska Katarzyna; Gumieniczek Anna; Filip Agata A. (Acta Pharmaceutica)
Results from numerous pre-clinical studies suggest that a well known anticonvulsant drug valproic acid (VPA) and other short-chain fatty acids (SCFAs) cause significant inhibition of cancer cell proliferation by modulating multiple signaling pathways. First of all, they act as histone deacetylase (HDAC) inhibitors (HDIs), being involved in the epigenetic regulation of gene expression. Afterward, VPA is shown to induce apoptosis and cell differentiation, as well as regulate Notch signaling. Moreover, it up-regulates the expression of certain G protein-coupled receptors (GPCRs), which are involved in various signaling pathways associated with cancer. As a consequence, some pre-clinical and clinical trials were carried out to estimate anticancer effectiveness of VPA, in monotherapy and in new drug combinations, while other SCFAs were tested in pre-clinical studies. The present manuscript summarizes the most important information from the literature about their potent anticancer activities to show some future perspectives related to epigenetic therapy.